A 3D graphene composite scaffold with a combinatorial fibrous-porous architecture for neural repair in the injured spinal cord - Girão, André Francisco Oliveira (2023)
Spinal cord injury continues to be, unarguably, a largely convoluted challenge of modern medicine, leaving millions of patients worldwide with devastating lifetime consequences. Currently, there are not medical treatments capable of efficiently and completely restoring lost autonomous, motor and/or sensory functions. In this context, along with the development of a next generation of biomedical platforms, the inclusion of graphene-based materials into neuroprotective and neuroregenerative strategies has potential to boost the structural and physiological recovery of the injured spinal cord. Particularly, these nanomaterials are updating important principles of tissue engineering concerning the development of biocompatible scaffolds suitable for replacing damaged neural microenvironments in a near-future scenario. In this work, a new design concept is used to fabricate graphene composites with fibrous-porous architectures able to support enhanced interactions with neural cells. In detail, electrospun nanofibres were accommodated onto the surface of reduced graphene oxide sheets to generate combinatorial 3D systems. The physiochemical and biological features of fibrous-porous constructs were associated with the properties of their nanofibrous coatings, resulting, consequently, in unique microenvironments capable of supporting highly viable, mature and interconnected neural circuits in vitro. Due to their enhanced performance, these graphene composites were further adapted to recreate the gray matter of the spinal cord, becoming a key component of a new biomimetic scaffolding methodology. In this way, for ensuring a spatial organization resembling the native spinal cord, where the center of gray matter is surrounded by white matter, the selected fibrous-porous graphene composite was incorporated within a 3D nanofibrous framework. Furthermore, specific regions of this biomimetic framework were loaded with polycaprolactone-chitosan nanofibres and polycaprolactone-graphene microfibers with the purpose of mimicking the white matter. After in vitro and ex vivo tests, the final biomimetic scaffold was then implanted into hemisected rats for 4 months, after which it was possible to observe promising neuroprotective and neuroregenerative features together with encouraging signs of forelimb function recovery. Based on these findings, the reported biomimetic graphene-based scaffolds hold potential to integrate advanced therapeutic strategies for countering spinal cord injury.